التراث وتوظيفه في تصميمات زخرفية معاصرة تطبيقا على أسقف أحد المساجد الحديثة - إبراهيم، إبراهيم بدوي; عثمان، عزة (الجمعية العربية للحضارة والفنون الإسلامية, 2021)
العقيدة الإسلامية ودورها في تشكيل وجدان الإنسان الفنان المسلم وتأثره وتأثيره في الحياة من حوله من أهم المقومات التي شكلت فنونه وأكسبتها مظهرها المميز واللافت للنظر وجوهرها القوي الثابت الذي استوعب في داخله فنون الدول التي دخلها الإسلام. هذان المظهر والجوهر اللذان يتحققا في فنون الزخرفة الإسلامية التي تحمل في طياتها تجسيد لأفكار العقيدة ومحاولات لتفسيرها، ويؤكدان على أصالة تلك الزخارف وانطلاقها من مجرد كونها خطوطا جمالية إلى اتجاهات تحمل أفكارا فلسفية مجردة هي روح الفنان المسلم وقلب إيمانه بالله الخالق. فالفنان المسلم اتخذ من عقيدته ومعناها شكلا وملمحا لزخرفته وفنونها من التوازن والتباين والوحدة والتنوع والارتباط والتداخل، فنراه يجسد فكرة أن المؤمنين إخوة في توادهم كالبنيان المرصوص في شكل فريد لعنصر معماري هو شرافات المساجد مؤكدا على معاني التساوي أمام الله والارتباط والقوة والثبات. ونراه يطبق زخارفه تلك على كل ما يحيط به بنفس الفكرة الأصيلة مع مراعاة تباين تقنيات التنفيذ ونسب المساحات ووظائفها، ونرى وحدته الزخرفية تزين سقف مسجده وقبته بنفس الجماليات التي تغلف بها مصحفه وتستقر بها على سجادة صلاته وتقف على مصرعي بابه وتعبر بها فتحات شبابيكه دون أن تغفل طبيعة الخامات المستخدمة لذلك من ملونات وصبغات طبيعية ومعادن وأخشاب وجص وزجاج في صياغة فنية جمالية تقنية بالغة الدقة والبساطة في آن واحد. ويتعرض البحث للأسقف المزخرفة كمثال على تجسيد الزخارف الإسلامية لأفكار العقيدة ومقوماتها ويشرح دور السقف كعنصر معماري وكمسطح قابل للتشكيل والزخرفة، ويتعرض البحث أيضا للملونات والصبغات الطبيعية وأنواع الأخشاب والتغطيات المستخدمة في تغطيات الأسقف في المساجد والمنازل الإسلامية. يقوم البحث كذلك بدراسة فنية تحليلية لبعض عناصر الزخارف الإسلامية النباتية والهندسية وإمكانيات تداخلها للوصول إلى تصميم زخرفي معاصر يمكن تطبيقه في أحد المساجد بما يؤكد على ثراء الزخارف الإسلامية وقابليتها للاستمرار والتجدد والنمو بصورة متوازية مع المعطيات التقنية الحديثة من خامات ومعدات والمقومات الأصيلة للتراث الإسلامي."
The Islamic faith and its role in shaping the consciousness of the Muslim artist and his influence and influence on life is one of the most important components that shaped it and earned it its distinctive and striking shape and its strong and stable essence that absorbed within it the arts that Islam entered. The belief in the appearance and essence that is achieved in the Islamic arts of decoration, which carries with it the embodiment of the ideas of belief and attempts to explain them, and confirms the originality of these decorations and their starting from mere aesthetic lines to an agreement of abstract philosophical ideas that are the spirit of the Muslim artist and the heart of his belief in God the Creator. The Muslim artist has taken from his faith and its meaning a form and a feature of his ornament and its arts, contrast, unity, diversity, connection and overlap, so we see him embody the idea that the believers are brothers in their closeness, like a structure in a unique form of an architectural age, which is the honor of mosques on the meanings of equality before God, connection, strength and stability. And we see him applying his decorations to everything that surrounds him with the same original idea, taking into account the variation in implementation techniques and the proportions of spaces and behind them, and we see his unity is a ceremony that adorns the roof of his mosque and its dome with the same aesthetics that envelop his Qur’an and his prayer rug settles with it and stands on Egypt overlooks it and crosses the openings of his windows without neglecting the industry Artistic, artistic, aesthetic, accuracy, and simplicity at the same time. The research deals with decorative ceilings as an example of the embodiment of Islamic motifs of the ideas of the faith and its constituents and explains the role as an architectural element and as a surface subject to formation and decoration, and the research is exposed to colorings, natural dyes, types of wood, and endings in ceiling coverings in mosques and homes."
Keywords: التصميم المعماري -- العمارة الإسلامية -- الزخرفة الإسلامية -- المساجد